Dampak poliposis hidung terhadap fungsi ventilasi paru - Poerbonegoro, Niken Lestari; Wardani, Retno Sulistyo; Dharmabakti, Umar Said; Rumende, Martin; Kusumayati, Agustin (Oto Rhino Laryngologica Indonesiana, 2010)
Background: Correlation between upper and lower airway always been an interesting topic in thepast decades, showed by the emerging of “one airway one disease” concept. Nasal polyposis is a chronicinflammatory disease of the upper respiratory tract mucosa. How nasal polyposis affects or relates to thelower respiratory tract is still debatable. Purpose: to evaluate the impact of nasal polyposis on the lowerrespiratory function.Methods: This study was done in the ENT Department and Pulmonology - InternalMedicine Department Cipto Mangunkusumo Hospital from March to December 2003. It was a comparativecross-sectional study between polyposis group and non-polyposis group, with 29 subjects each. Subjectsunderwent skin prick test and spirometry examinations. Vital capacity (VC), forced expiratory volumeat the first one second (FEV1) and FEV1Dampak poliposis hidung terhadap fungsi ventilasi paru1/VC ratio values were gathered. Statistic calculations performed using independents t-test and Pearson chi-square.Results: Spirometry datas showed VC %prediction andFEV%prediction values in nasal polyposis group were lower than in non-polyposis group (68.33% and62.36% vs 78.66% and 70.65%, p < 0.05), but not significant for FEV1061 /VC ratio score  (83.88 vs 83.18,p > 0.05). Patterns of lung ventilatory function, the percentage of lung ventilatory function disorderbetween the polyposis group and the control group is significantly different (58.7% vs 31%, p< 0.05).Using 2x2 table calculation, prevalence ratio was 1.9 (CI 95% 0.002-0.498).Conclusion: Polyposisgroup showed significant lower values of VC % prediction and FEV1 1% prediction. Percentage of lungventilatory function disorder in polyposis group is significantly higher than control.Keywords: nasal polyposis, lung ventilatory function, spirometry, VC, FEV Abstrak : Latar belakang: Beberapa dekade terakhir ini hubungan antara saluran napas atas dan bawah tetaphangat dibicarakan, ditandai dengan munculnya konsep “one airway one disease”. Poliposis hidungmerupakan keadaan inflamasi kronis mukosa saluran napas atas. Bagaimana kaitan poliposis hidungdengan saluran napas bawah sampai saat ini masih dipertanyakan. Tujuan: Mengetahui dampakpoliposis hidung terhadap fungsi ventilasi paru. Metode: Desain studi adalah potong lintang komparatifantara kelompok penderita poliposis hidung dan kelompok tanpa poliposis hidung. Jumlah percontohsetiap kelompok sebesar 29 orang. Dilakukan tes cukit kulit dan pemeriksaan spirometri untuk menilaifungsi ventilasi paru. Nilai persentase prediksi kapasitas vital paksa (KVP), volume ekspirasi paksa detikpertama (VEP1), dan rasio VEP/KVP dicatat. Perhitungan statistik dilakukan dengan uji t-independendan Pearson chi-square. Hasil: Hasil spirometri memperlihatkan nilai rerata % prediksi KVP dan nilairerata % prediksi VEP1 1 kelompok penderita poliposis hidung lebih rendah dari kelompok tanpa poliposishidung (68,33% dan 62,36% banding 78,66% dan 70,65%; p< 0,05). Nilai rasio VEP/KVP kelompokpasien poliposis hidung sedikit lebih tinggi dari kelompok tanpa poliposis hidung (83,88 banding 83,18;p>0,05). Data gambaran fungsi ventilasi paru memperlihatkan perbedaan yang bermakna pada proporsigangguan fungsi ventilasi paru antara kedua kelompok (58,7% dan 31%, p<0,05). Dengan perhitungantabel 2x2 didapatkan rasio prevalens sebesar 1,9 (IK 95% 0,002-0,498).Kesimpulan: kelompok denganpoliposis hidung memperlihatkan penurunan bermakna nilai % prediksi KVP dan % prediksi VEP, namunrasio VEP/KVP tidak menurun. Proporsi gangguan fungsi ventilasi paru pada kelompok poliposis hidunglebih besar daripada kelompok tanpa poliposis hidung.1Kata kunci: poliposis hidung, fungsi ventilasi paru, spirometri, KVP, VEP